2011
DOI: 10.1682/jrrd.2010.09.0190
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of daily step activity monitoring in adults with incomplete spinal cord injury

Abstract: Abstract-We determined the number of days of step activity monitoring required to establish stable measures of walking activity in adults with incomplete spinal cord injury (iSCI). Eleven individuals with iSCI (mean age 49 +/-14 years) wore a StepWatch Activity Monitor during waking hours for 7 consecutive days. We used generalizability theory to identify sources of variance in daily step counts and determine the minimum number of days necessary to obtain a reliability coefficient (G-coefficient) greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…This was replicated by Norris et al [23], who reported similar findings using an approach that examined reliability coefficients from random 2-day to 7-day averages. In addition, obtaining a stable measure of freeliving walking activity based on pedometer use may require 7 days in healthy individuals [33], while more impaired populations such as incomplete spinal cord injury patients may require only 2 days of monitoring to achieve acceptably stable estimates [34]. This finding has practical implications with respect to utilizing wearable generated activity data in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…This was replicated by Norris et al [23], who reported similar findings using an approach that examined reliability coefficients from random 2-day to 7-day averages. In addition, obtaining a stable measure of freeliving walking activity based on pedometer use may require 7 days in healthy individuals [33], while more impaired populations such as incomplete spinal cord injury patients may require only 2 days of monitoring to achieve acceptably stable estimates [34]. This finding has practical implications with respect to utilizing wearable generated activity data in clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…The relative magnitude of error in step counts for each term was computed by dividing the estimate of the single variance component by the total variance and multiplying by 100. 10 …”
Section: Methodsmentioning
confidence: 99%
“…The generalizability theory (G theory) has been applied in different populations to determine the number of days that is sufficient to achieve an acceptable reliability coefficient. 1012 The G theory is unique in that it allows the researchers to identify the relative contribution of different sources of variance to total variance in measurement. 13,14 The findings of the studies by Ishikawa et al 10 demonstrated that 2 days were necessary to reliably measure daily PA of adults with incomplete spinal cord injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Levels of walking activity using pedometers require about 7 days of data collection to obtain a stable and representative average for healthy persons 49 to as little as 2 days for those with incomplete SCI. 50 For a clinical trial of a walking intervention of 3 months duration, a minimal data set might include 2 weeks of daily monitoring prior to starting the comparison treatments, then for one week monthly or at the time of scheduled outcome measures. For a drug trial, activity might be measured continuously for at least a month – two weeks prior and at least 2 weeks after initiation to detect fluctuations in response to medications (e.g., dyskinesias or freezing of gait in Parkinson's disease, leg spasms in SCI).…”
Section: Sensors For Clinical Trialsmentioning
confidence: 99%